Efficacy of three trap crops against whitefly to manage tomato yellow leaf curl virus - Muqit, Abdul; Akanda, Abdul Mannan; Alam, Mohammed Zinnatul (Bangladesh Journal of Agricultural Research, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> doi:10.3329/bjar.v33i3.1610 Bangladesh J. Agril. Res. 33(3) : 515-517, September 2008